Pemanfaatan Sepeda Statis Dengan Generator Linier Untuk Pembangkit Listrik Ramah Lingkungan - Purnomo, Aji, Ir. Jatmiko, MT (2016)
Electrical energy is energy which is one of the basic necessities of human life. The use of electricity for household, industrial and even transportation. Many areas in Indonesia who can not feel the electricity, therefore do the construction of power plants is very important. Bicycles which is one of the means of transportation in Indonesia can be used as a power plant. This study will discuss the use of a stationary bike as the driver of the linear generator windings and analyze the effect on the output voltage. Using a linear generator stator frame 6 slot with the number of windings 300, 500 and 800 winding and rotor using a permanent magnet-type ferrite amounting to 5 pairs of copper wire with a diameter of 0.4 mm. The lowest voltage generated 3.1 volts at 100 rpm with a number of loops 300 and the highest voltage of 14.4 volts at a speed of 300 rpm with a number of windings 800. The data were taken from experiments conducted by the laboraturium scale, can be developed to a larger scale so that it can generate power the greater one. Keywords: linear generator, a permanent magnet, environmentally friendly, bikes